Screening and Characterization of raw starch degrading amylase (RSDA) from locally isolated fungal strains in Unimas fungal collection - Voon, Siew Fung (University Malaysia Sarawak, UNIMAS., 2013)
Raw starch degrading amylase (RSDA) is the enzyme that catalyst the breakdown of starch into simple sugar by cleaves the bonds between the adjacent glucose units which lead to the formation of linear and branched oligosaccharides. Six isolated fungal strains namely Bionectria ochroleuca, Trichoderma harzianum, Trichoderma virens, Aspergillus versicolor, Aspergillus niger and Aspergillus flavus were screened for their ability to hydrolyze raw sago starch by producing the RSDA through qualitative and quantitative test. Characterizations were carried out and the strains were compared for their degradative ability on raw and gelatinized sago starch, substrate specificity and preferred pH for the reaction medium. Results showed that A. flavus was the best performing strain that produced the highest amount of RSDA and it has the broad activity toward both small and large granule of raw starches.